ChemInform Abstract: Cooperative Effect in Organocatalytic Intramolecular Hydroamination of Unfunctionalized Olefins. Issue 42 (14th October 2014) - Wang, Yu‐Mei; Li, Ting‐Ting; Liu, Gong‐Qing; Zhang, Li; Duan, Lili; Li, Lin; Li, Yue‐Ming
Abstract A variety of organic acids are tested for the hydroamination.